Pengaruh Intellectual Capital, Non Performing Financing (NPF), & Financing To Deposit Ratio (FDR) terhadap Kinerja Keuangan Bank Syariah Tahun 2014-2018 - Caesar, Jenny Aghnia; Isbanah, Yuyun (Jurnal Ilmu Manajemen, 2020)
The development of the financial performance of Islamic banks in Indonesia in the 2014-2018 period has increased and developed over the past twenty years, the development of Islamic banks' financial performance has not met the targeted expectations of above 5% (ojk.go.id). Judging from the market share of Islamic banks have met the target but it is caused by the conversion of conventional banks into sharia and not because of organic growth (www.infobanknews.com). Compared to conventional banks, Islamic banks only channeled total loans of Rp 291.18 trillion from Rp 4,782 trillion of total national banking loans or only 6.08% of total national banking loans which caused the growth of the Islamic finance industry to slow down. So this study intends to see the effect of intellectual capital, non-performing financing (NPF), and financing to deposit ratio (FDR) on the financial performance of Islamic banks. This study uses multiple linear regression analysis techniques with a sample of all Islamic banks registered at the OJK and meets the specified criteria to produce as many as 8 Islamic banks that are eligible to be tested. The results of this study indicate that the variables HCE, SCE, CEE and FDR do not affect ROA while the NPF variable is the only variable that has a negative influence on ROA. Customers use the NPF value to see whether the bank can return credit from a bank's debtors, a high NPF value indicates the level of bank failure in returning credit that negatively impacts ROA.